1995
DOI: 10.1038/nm1295-1279
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of the CD4/CD8 T-cell ratio in humans

Abstract: We studied the genetic pattern of inheritance of the ratio between circulating CD4+ and CD8+ T lymphocytes in a population of healthy donors. The distribution of the CD4/CD8 ratio in males and females was significantly different and was significantly affected by age. In 46 randomly selected families, the parental CD4/CD8 ratio significantly influenced the ratio in offspring. Complex segregation analysis of the data rejected the non-genetic hypothesis; among the genetic models tested, a major recessive gene wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
257
1
7

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 399 publications
(294 citation statements)
references
References 22 publications
24
257
1
7
Order By: Relevance
“…However, differences in immune cell subsets are less striking, with 10% higher absolute CD4 T cell counts in women being the most clear cellular difference between men and women [31]. It is tempting to speculate that the difference in V § 24 NKT cells between women and men may suggest a link between the immunoregulatory NKT cells and the sexual dimorphism of diseases in which these cells seem to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in immune cell subsets are less striking, with 10% higher absolute CD4 T cell counts in women being the most clear cellular difference between men and women [31]. It is tempting to speculate that the difference in V § 24 NKT cells between women and men may suggest a link between the immunoregulatory NKT cells and the sexual dimorphism of diseases in which these cells seem to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence for their role in the regulation of the inflammatory response through the release of cytokines [20,21]. A recent study has demonstrated genetic control of the ratio between CD8+ and CD4+ cells with a small (5%) percentage of the population having a CD4/CD8 ratio of <1 [22]. The current data would be consistent with the hypothesis, suggested by O'SHAUGHNESSY et al [8], that those with a genetically determined increase in the CD8+ population may be more susceptible to a further increase in CD8+ cells induced by smoking.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Although environmental and other factors may affect the numbers of CD4 to CD8 T cells in an individual, it is clear that the ratio is also under genetic control. [12][13][14] Since the maturation of CD4 and CD8 T cells is controlled by interactions of their ␣␤ T cell receptors with class II and class I major histocompatibility complex proteins (MHC) and peptides in the thymus, one would predict that CD4 to CD8 ratios would be affected by TCR and MHC genes. Indeed there is evidence that in certain mouse strain combinations, this is the case.…”
Section: Introductionmentioning
confidence: 99%